"Aprender y no olvidar. Reflexiones acerca de los desastres". Revuelta, F. y Calvo Poyato, J. (2022). - Gomez Baya, Diego (Análisis y Modificación de Conducta, 2023)
Revuelta, F., y Calvo Poyato, J. (2022). Aprender y no olvidar. Reflexiones acerca de los desastres. Editorial Tecnos.